Case Report: Glucose transporter 1 deficiency syndrome misdiagnosed as bacterial meningitis - Wang, Man; Wang, Cuijin; Shang, Li; Feng, Yamei; Huang, Dandan; Li, Qin; Wang, Jiwen; Guo, Hui; Wang, Yingyan (Frontiers in Pediatrics, 2026)
BackgroundGlucose transporter 1 deficiency syndrome (Glut1DS), caused by SLC2A1 gene variants, is a rare neurological disorder with diverse clinical features and is highly susceptible to misdiagnosis or missed diagnosis. This article described two infant cases of Glut1DS misdiagnosed as bacterial meningitis due to atypical presentations, emphasizing the importance of early recognition.MethodRetrospective analysis of two patients with Glut1DS admitted to our hospital between July 2023 and July 2025. Clinical features, cerebrospinal fluid (CSF) profiles, genetic testing, and responses to ketogenic diet (KD) were evaluated. Both cases were preliminarily diagnosed with bacterial meningitis in local hospitals based on low CSF glucose levels.ResultsCase 1: A 15-day-old male infant with fever and lethargy had persistently low CSF glucose (1.2–1.64 mmol/L; CSF/blood glucose ratio: 0.22–0.32). He was diagnosed as atypical bacterial meningitis and underwent empirical antibiotic therapy lasting over 30 days. Genetic testing confirmed SLC2A1 variant and KD greatly improved neurodevelopment. Case 2: A 4-month-old infant with fever and recurrent seizures showed persistent CSF hypoglycorrhachia (1.1–1.37 mmol/L; CSF/blood glucose ratio: 0.19–0.36). Following unsuccessful empirical antibiotic therapy, genetic analysis revealed a pathogenic variant in SLC2A1. Seizure resolution and EEG improvement were achieved after KD therapy.Conclusionlow CSF glucose is a critical diagnostic clue for Glut1DS, not exclusive to CNS infections. In infants with seizures, developmental delays, or motor dysfunction, CSF analysis and targeted SLC2A1 testing are essential. Early KD initiation upon clinical suspicion may significantly improve outcomes and prevents neurological deterioration.